Efektifitas Media Konvensional Dalam Aktivitas Dakwah: (Studi Pada Eksistensi Radio Dakwah Ahbabul Musthofa Krejengan Probolinggo) - Rofia, Siti; Mutrofin, Mutrofin (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
AConventional media is media that was discovered first before the discovery of new media. This media is also called mass media because this media is used to send messages, information, news. In addition, radio is also used as a medium of da'wah. Ahbabul Musthofa is one of the da'wah radios which is currently still operating, the use of radio as a da'wah media is a way to expand the reach of da'wah. The purpose of this research is to find out how effective radio is as a propaganda medium in the digital era. This study uses a qualitative research method, this method requires researchers to go directly to the research location to collect data through interviews, documentation as evidence from this research. From this research, da'wah radio is very helpful for the community in getting to know the teachings of the Islamic religion, even though currently the existence of radio has been competed with the presence of other audio visuals. However, the people of Probolinggo and its surroundings still use radio to get information as well as spiritual guidance, the existence of da'wah radio is very helpful for the people of Probolinggo.